PENGARUH PENDIDIKAN TERHADAP PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DI DESA NAEKAKE A KECAMATAN MUTIS KABUPATEN TIMOR TENGAH UTARA - Metriana Elu; Detson R.H Sitorus; Marthen Patiung (JianE (Jurnal Ilmu Administrasi Negara), 2025)
The issue in this research is whether there is an influence of education on community participation. This study aims to determine the influence of education on community participation in development in Naekake A Village, Mutis District, North Central Timor Regency. This type of research uses quantitative research methods. The population in this study totaled 1,734 people and the sample consisted of 95 individuals. This research was conducted in Naekake A Village, Mutis District, North Central Timor Regency. The data sources come from primary and secondary data. Data collection techniques used questionnaires, observations, and documentation. Data analysis techniques use Spearman Rank Correlation and the Coefficient of Determination (R2). The research results indicate that there is an influence between education and community participation in development in Naekake A Village of 17.5%, while the remaining 82.5% is influenced by other variables outside this research model.